Development of an equivalent static method for the approximation of the dynamic response of offshore structures. Issue 4 (5th June 2019) - Koukouselis, Apostolos; Chatziioannou, Konstantinos; Mistakidis, Euripidis; Katsardi, Vanessa
Abstract : Purpose: The design of compliant towers in deep waters is greatly affected by their dynamic response to wave loads as well as by the geometrical and material nonlinearities that appear. In general, a nonlinear time history dynamic analysis is the most appropriate one to be applied to capture the exact response of the structure under wave loading. However, this type of analysis is complex and time-consuming. This paper aims to develop a simplified methodology, which can adequately approximate the maximum response yielded by a dynamic analysis by means of a static analysis. Design/methodology/approach: Various types of time history dynamic analysis are first applied on a detailed structural model, ranging from linear to fully nonlinear, that are used as reference solutions. In the sequel, a simplified analysis model is formulated, capable of reproducing the response of the entire structure with significantly reduced computational cost. In the next stage, this model is used to obtain the linear and nonlinear response spectra of the structure. Finally, these spectra are used to formulate a simplified design approach, based on equivalent static loads. Findings: This simplified design approach produces good results in cases that the response is mainly governed by the first eigenmode, which is the case when compliant towers are considered. Originality/value: The present paper borrows ideas from the area of earthquake engineering, where simplified methodologies can be used for the design of a certain class of structures. However, the development of a simplified methodology for the approximation of the dynamic behavior of offshore structures under wave loading is a much more complex problem, which, to the authors' knowledge, has not been addressed till now.